Pengambangan LKPD berbasis Pembelajaran RADEC untuk Meningkatkan Pemahaman Konsep dan Kemandirian Belajar - Milaningsih, Marlita Diah; Sartono, E. Kus Eddy (Jurnal Pendidikan Indonesia, 2025)
One of the most critical learning tools is the Student Worksheet (LKDP). The LKPD used needs to improve students' conceptual understanding and learning independence, especially in Pancasila Education. Pancasila Education prepares students as citizens who master knowledge, skills, attitudes, and values. This study aims to analyze the validity, practicality, and effectiveness of RADEC Learning-based LKPD to improve conceptual understanding and learning independence. The research method used is research and development (R&D) with the Borg and Gall development model. The research subjects were fourth-grade elementary school students. Data collection techniques used in this study were tests and non-tests, namely interviews, tests, observations, and questionnaires. The data obtained were then analyzed for validity, practicality, and effectiveness through pre-tests, t-tests, MANOVA tests, and N-Gain scores. The results of the n-gain score analysis showed that the n-gain scores for conceptual understanding and learning independence were higher in the experimental class compared to the control class. The t-test and Manova test results at a significance level of 0.05 showed that student worksheets based on RADEC learning significantly influenced the conceptual understanding and learning independence of fourth-grade elementary school students, with significance values of 0.003 and 0.000 (p<0.005). RADEC-based student worksheets have been proven effective in improving students' conceptual understanding and learning independence.